Culture: People to Water (Symphony in the Flint Hills, 2018)
Introduction: The great inland ocean had long since receded when the first peoples gazed across the Sea of Grass. For thousands of years, they lived along clear streams full of water and fish. But the precious resource drew waves of new inhabitants who lacked the epoch cultural ties to the grassland.